Corrosion-resistant inflatable PVC film and preparation method thereof

By using modified nanotitanium dioxide and phenolic resins in PVC films, the problem of corrosion susceptibility of traditional PVC films is solved, the corrosion resistance and service life are improved, and the mechanical properties and thermal stability are enhanced.

CN119264577AInactive Publication Date: 2025-01-07广东鑫佰威新材料科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411454037.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PVC membranes are susceptible to corrosive gases and liquids on greenhouses and irrigation system pipelines, resulting in a shorter service life.

Method used

Using modified nanotitanium dioxide and phenolic resins, the compatibility and dispersion of nanotitanium dioxide and PVC substrates are improved by grafting polypropylene and KH550 in maleic anhydride, forming a spatial network structure, filling the defects of PVC films, and sluggish resistance. Infiltration of corrosive substances.

Benefits of technology

It significantly improves the corrosion resistance of PVC films, extends service life, and enhances mechanical properties and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005089957210000061
    Figure BDA0005089957210000061
  • Figure BDA0005089957210000071
    Figure BDA0005089957210000071
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant inflatable PVC film and a preparation method thereof, and relates to the field of PVC films. The corrosion-resistant inflatable PVC film comprises the following raw materials in parts by weight: 80-120 parts of PVC; 20-40 parts of a plasticizer; 10-20 parts of a stabilizer; 10 to 20 parts of modified nano titanium dioxide; 5-15 parts of phenolic resin; the modified nano titanium dioxide is prepared from nano titanium dioxide, KH550, maleic anhydride grafted polypropylene and deionized water. The corrosion-resistant PVC film has the effect of improving the corrosion resistance of the PVC film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of PVC films, and in particular to a corrosion-resistant inflatable PVC film and a preparation method thereof. Background Art

[0002] At present, PVC has good electrical insulation, flame retardancy and plasticity, and is widely used in cables, shoes, packaging films, pipes and some daily necessities. PVC film is widely used in various packaging, protection and covering materials due to its excellent physical properties and processing properties.

[0003] However, traditional PVC membranes need to be laid on pipes in greenhouses and irrigation systems. During long-term use, they are easily affected by environmental factors, especially corrosive gases and liquids, which shortens their service life. Summary of the invention

[0004] In order to improve the corrosion resistance of PVC film, the present application provides a corrosion-resistant inflatable PVC film and a preparation method thereof.

[0005] In the first aspect, the present application provides a corrosion-resistant inflatable PVC membrane adopting the following technical solution: A corrosion-resistant inflatable PVC film comprises the following raw materials in parts by weight: 80-120 parts of PVC; 20-40 parts of plasticizer; 10-20 parts of stabilizer; 10-20 parts of modified nano titanium dioxide; and 5-15 parts of phenolic resin. The modified nano titanium dioxide comprises nano titanium dioxide, KH550, maleic anhydride grafted polypropylene and deionized water.

[0006] By adopting the above technical scheme, PVC is used as the substrate, and the phenolic resin evenly disperses the modified titanium dioxide on the surface of PVC, so that the modified nano titanium dioxide is not easy to agglomerate. The modified titanium dioxide is grafted with maleic anhydride polypropylene and KH550 to improve the compatibility and dispersibility of nano titanium dioxide with the PVC substrate, thereby further improving the corrosion resistance of the PVC substrate.

[0007] Preferably, the preparation method of the modified nano titanium dioxide is: 20-30 parts by weight of nano titanium dioxide, 10-15 parts by weight of KH550, 55-70 parts by weight of maleic anhydride grafted polypropylene and 20-40 parts by weight of deionized water are stirred at a speed of 500-600 r / min for 5-10 minutes, and the modified nano titanium dioxide is obtained after filtering and drying.

[0008] By adopting the above technical scheme, nano titanium dioxide is mixed with maleic anhydride grafted polypropylene and KH550, and the nano titanium dioxide is uniformly dispersed in the maleic anhydride grafted polypropylene through physical and chemical methods. KH550 grafts the nano titanium dioxide so that the nano titanium dioxide and the maleic anhydride grafted polypropylene are combined through chemical bonds to form a spatial network structure. The modified nano titanium dioxide is added to the PVC film component to effectively fill the defects in the PVC film, slow down the penetration of corrosive substances, and thus improve the corrosion resistance of the PVC film.

[0009] Preferably, the weight ratio of the nano titanium dioxide, KH550 and maleic anhydride grafted polypropylene is 1: (0.48-0.56): (1.28-1.44).

[0010] By adopting the above technical scheme, when nano titanium dioxide, KH550 and maleic anhydride grafted polypropylene are in a specific weight ratio, nano titanium dioxide is not easy to agglomerate, nano titanium dioxide can be better dispersed and combined with maleic anhydride grafted polypropylene, the two have better compatibility, which helps to reduce the porosity of the PVC film, thereby improving the corrosion resistance of the PVC film.

[0011] Preferably, the particle size of the nano titanium dioxide is in the range of 800-1000 mesh.

[0012] By adopting the above technical solution, the pore filling rate can be improved by selecting nano titanium dioxide with a suitable particle size range, so that the nano titanium dioxide has a larger specific surface area, and effectively prevents the corrosion of corrosive substances to the PVC film.

[0013] Preferably, the PVC is modified PVC, wherein the preparation method of the modified PVC is: after mixing 80-120 parts by weight of PVC and 50-70 parts by weight of dioctyl terephthalate for 10-20 minutes, adding 2-8 parts by weight of nano calcium carbonate, heating to 100-120° C. and continuing to stir for 5-10 minutes, then adding 1-3 parts by weight of calcium stearate and stirring evenly, cooling to 60-65° C. and plasticizing for 5-10 minutes to obtain the modified PVC.

[0014] By adopting the above technical scheme, PVC and stearate are compounded by a physical blending method. Nano calcium carbonate has a large specific surface area and can be effectively dispersed on the surface of PVC to form a good interface bonding. Dioctyl terephthalate is compatible with PVC molecules, which reduces the interaction force between PVC molecules, increases the plasticity of PVC, and helps to improve the chemical corrosion resistance of PVC. Calcium stearate can interact with the polar groups on the PVC molecular chain through chemical bonding, improve the thermal stability of PVC, reduce the thermal decomposition of PVC during processing, and thus improve the corrosion resistance of the PVC film.

[0015] Preferably, the weight ratio of PVC, dioctyl terephthalate, nano calcium carbonate and calcium stearate is 1: (0.64-0.66): (0.056-0.072): (0.012-0.015).

[0016] By adopting the above technical scheme, when PVC, dioctyl terephthalate, nano calcium carbonate and calcium stearate are in a specific weight ratio, the four cooperate together and the amount of calcium stearate is increased. The lubricating effect of calcium stearate can make PVC less likely to adhere during the processing process, and at the same time, it can have a wetting effect on the nano calcium carbonate, so that the fluidity of the nano calcium carbonate is improved, and it can be evenly distributed in the PVC, so that the mechanical strength and thermal stability of the modified PVC are further improved.

[0017] Preferably, the weight ratio of the modified PVC, modified nano titanium dioxide and phenolic resin is 1: (0.16-0.18): (0.06-0.08).

[0018] By adopting the above technical scheme, the modified nano titanium dioxide is modified by maleic anhydride grafting polypropylene, and the hydroxyl and amino groups in the phenolic resin can react with the anhydride groups in the maleic anhydride to connect the maleic anhydride grafted polypropylene with the modified nano titanium dioxide; at the same time, the phenolic resin interacts with the polar groups on the PVC chain, thereby enhancing the compatibility between PVC and nano titanium dioxide, thereby improving the mechanical properties and thermal stability of the PVC film.

[0019] Preferably, the plasticizer is selected from one of dioctyl phthalate and dioctyl adipate.

[0020] By adopting the above technical solution and selecting a suitable plasticizer, the plasticity and softness of the PVC film are improved, making the PVC film easier to process and use.

[0021] Preferably, the stabilizer is selected from one of barium stearate and zinc stearate.

[0022] By adopting the above technical solution and selecting a suitable stabilizer, it is possible to prevent PVC from being degraded during processing and use, thereby extending the service life of the PVC film.

[0023] In the second aspect, the present application provides a method for preparing a corrosion-resistant inflatable PVC film using the following technical scheme: a method for preparing a corrosion-resistant inflatable PVC film, comprising the following steps: mixing and stirring PVC, a plasticizer, a stabilizer, modified nano titanium dioxide and a phenolic resin, plasticizing and refining the mixture, calendering, cooling and winding the mixture after extrusion to obtain the corrosion-resistant inflatable PVC film.

[0024] In summary, this application has the following beneficial technical effects: 1. PVC is used as the substrate, and phenolic resin evenly disperses the modified titanium dioxide on the surface of PVC, making it difficult for the modified nano titanium dioxide to agglomerate. The modified titanium dioxide is grafted with maleic anhydride polypropylene and KH550 to improve the compatibility and dispersibility of nano titanium dioxide with the PVC substrate, thereby further improving the corrosion resistance of the PVC substrate.

[0025] 2. Mix nano titanium dioxide with maleic anhydride grafted polypropylene and KH550, and evenly disperse the nano titanium dioxide in the maleic anhydride grafted polypropylene through physical and chemical methods. KH550 grafts the nano titanium dioxide so that the nano titanium dioxide and the maleic anhydride grafted polypropylene are combined through chemical bonds to form a spatial network structure. The modified nano titanium dioxide is added to the PVC film component to effectively fill the defects in the PVC film, slow down the penetration of corrosive substances, and thus improve the corrosion resistance of the PVC film. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to examples and comparative examples. Example

[0027] Example 1 A method for preparing a corrosion-resistant inflatable PVC film comprises the following steps: 80g PVC, 20g plasticizer, 10g stabilizer, 10g modified nano titanium dioxide and 5g phenolic resin were put into a high-speed mixer, stirred at 90°C for 10 minutes, transferred to a planetary mixer, and the temperature of the planetary mixer was controlled at 140°C to make the PVC plasticized evenly and then transferred to an open plastic purifying machine. The material of the open mill was directly fed to a calender at a temperature of 165°C after filtering impurities through a single screw filter, and a corrosion-resistant inflatable PVC film was obtained through calendering, cooling and winding. The plasticizer is dioctyl phthalate, the stabilizer is zinc stearate, the PVC is made of German vinnolit, model EP7060, and the phenolic resin is made of Jining Sanshi Biotechnology Co., Ltd., model SH-7301694.

[0028] The preparation method of the modified nano titanium dioxide is as follows: 20g of nano titanium dioxide, 10g of KH550, 55g of maleic anhydride grafted polypropylene and 20g of deionized water are stirred at a speed of 500r / min for 5min, filtered and dried in an oven at a temperature of 100°C for 24h to obtain the modified nano titanium dioxide. The particle size of the nano titanium dioxide is 1000 mesh, and the maleic anhydride grafted polypropylene is selected from DuPont of the United States, model 50E806.

[0029] Example 2 A method for preparing a corrosion-resistant inflatable PVC film comprises the following steps: 120g PVC, 40g plasticizer, 20g stabilizer, 20g modified nano titanium dioxide and 15g phenolic resin were put into a high-speed mixer, stirred at 90°C for 10 minutes, transferred to a planetary mixer, and the temperature of the planetary mixer was controlled at 140°C to make the PVC plasticized evenly and then transferred to an open plastic purifying machine. The material of the open purifying machine was directly fed to a calender at a temperature of 165°C after filtering impurities through a single screw filter. After calendering, cooling and winding, a corrosion-resistant inflatable PVC film was obtained. The plasticizer was dioctyl adipate, the stabilizer was zinc stearate, the PVC was selected from German vinnolit, model EP7060, and the phenolic resin was selected from Jining Sanshi Biotechnology Co., Ltd., model SH-7301694.

[0030] The preparation method of the modified nano titanium dioxide is as follows: 20g of nano titanium dioxide, 10g of KH550, 55g of maleic anhydride grafted polypropylene and 20g of deionized water are stirred at a speed of 500r / min for 5min, filtered and dried in an oven at a temperature of 100°C for 24h to obtain the modified nano titanium dioxide. The particle size of the nano titanium dioxide is 1000 mesh, and the maleic anhydride grafted polypropylene is selected from DuPont of the United States, model 50E806.

[0031] Example 3 A method for preparing a corrosion-resistant inflatable PVC film comprises the following steps: 100g PVC, 30g plasticizer, 15g stabilizer, 15g modified nano titanium dioxide and 10g phenolic resin were put into a high-speed mixer, stirred at 90°C for 10 minutes, transferred to a planetary mixer, and the temperature of the planetary mixer was controlled at 140°C to make the PVC plasticized evenly and then transferred to an open plastic purifying machine. The material of the open purifying machine was directly fed to a calender at a temperature of 165°C after filtering impurities through a single screw filter. After calendering, cooling and winding, a corrosion-resistant inflatable PVC film was obtained. The plasticizer was dioctyl phthalate, the stabilizer was barium stearate, the PVC was made by German vinnolit, model EP7060, and the phenolic resin was made by Jining Sanshi Biotechnology Co., Ltd., model SH-7301694.

[0032] The preparation method of the modified nano titanium dioxide is as follows: 20g of nano titanium dioxide, 10g of KH550, 55g of maleic anhydride grafted polypropylene and 20g of deionized water are stirred at a speed of 500r / min for 5min, filtered and dried in an oven at a temperature of 100°C for 24h to obtain the modified nano titanium dioxide. The particle size of the nano titanium dioxide is 1000 mesh, and the maleic anhydride grafted polypropylene is selected from DuPont of the United States, model 50E806.

[0033] Example 4 A method for preparing a corrosion-resistant inflatable PVC membrane, which is different from Example 3 in that: in the process of preparing modified nano titanium dioxide: 30g of nano titanium dioxide, 15g of KH550, 70g of maleic anhydride grafted polypropylene and 40g of deionized water are stirred at a speed of 600r / min for 10min, filtered and dried in an oven at a temperature of 100°C for 24h to obtain modified nano titanium dioxide.

[0034] Example 5 A method for preparing a corrosion-resistant inflatable PVC film, which is different from Example 3 in that: in the process of preparing modified nano-titanium dioxide, the input amount of nano-titanium dioxide is 25g, the input amount of KH550 is 12g, and the input amount of maleic anhydride grafted polypropylene is 32g.

[0035] Example 6 A method for preparing a corrosion-resistant inflatable PVC film, which is different from Example 3 in that: in the process of preparing modified nano-titanium dioxide, the input amount of nano-titanium dioxide is 25g, the input amount of KH550 is 14g, and the input amount of maleic anhydride grafted polypropylene is 36g.

[0036] Example 7 A method for preparing a corrosion-resistant inflatable PVC film, which is different from Example 6 in that an equal amount of PVC is replaced with modified PVC, wherein the preparation method of the modified PVC is as follows: 80g of PVC and 50g of dioctyl terephthalate are mixed and stirred for 10 minutes, 2g of nano-calcium carbonate is added, the temperature is raised to 100°C and stirring is continued for 5 minutes, and then 1g of calcium stearate is added and stirred evenly, and the temperature is lowered to 60°C and plasticized for 5 minutes to obtain the modified PVC.

[0037] Example 8 A method for preparing a corrosion-resistant inflatable PVC film, which is different from Example 6 in that an equal amount of PVC is replaced with modified PVC, wherein the preparation method of the modified PVC is as follows: 120g of PVC and 70g of dioctyl terephthalate are mixed and stirred for 20 minutes, 8g of nano-calcium carbonate is added, the temperature is raised to 120°C and stirring is continued for 10 minutes, and then 3g of calcium stearate is added and stirred evenly, the temperature is lowered to 65°C and plasticized for 10 minutes to obtain the modified PVC.

[0038] Example 9 A method for preparing a corrosion-resistant inflatable PVC film, which is different from Example 8 in that: in the process of preparing the modified PVC, the input amount of PVC is 100g, the input amount of dioctyl terephthalate is 64g, the input amount of nano-calcium carbonate is 5.6g, and the input amount of calcium stearate is 1.2g.

[0039] Example 10 A method for preparing a corrosion-resistant inflatable PVC film, which is different from Example 8 in that: in the process of preparing the modified PVC, the input amount of PVC is 100g, the input amount of dioctyl terephthalate is 66g, the input amount of nano-calcium carbonate is 7.2g, and the input amount of calcium stearate is 1.5g.

[0040] Embodiment 11 A method for preparing a corrosion-resistant inflatable PVC film, which is different from Example 10 in that the input amount of modified PVC is 100g, the input amount of modified nano titanium dioxide is 16g, and the input amount of phenolic resin is 6g.

[0041] Example 12 A method for preparing a corrosion-resistant inflatable PVC film, which is different from Example 10 in that the input amount of modified PVC is 100g, the input amount of modified nano titanium dioxide is 18g, and the input amount of phenolic resin is 8g.

[0042] Comparative Example Comparative Example 1 A method for preparing a corrosion-resistant inflatable PVC membrane, which is different from Example 3 in that an equal amount of modified nano titanium dioxide is replaced by nano titanium dioxide.

[0043] Comparative Example 2 A method for preparing a corrosion-resistant inflatable PVC membrane, which is different from Example 3 in that an equal amount of modified nano-titanium dioxide is replaced by nano-silicon dioxide.

[0044] Comparative Example 3 A method for preparing a corrosion-resistant inflatable PVC membrane, which is different from Example 3 in that no phenolic resin is added.

[0045] Comparative Example 4 A method for preparing a corrosion-resistant inflatable PVC membrane, which is different from Example 3 in that an equal amount of phenolic resin is replaced by epoxy resin.

[0046] Performance testing: Tensile strength test: The corrosion-resistant inflatable PVC membranes prepared in Examples 1-12 and Comparative Examples 1-4 were tested according to GB / T 1040.3-2006.

[0047] Corrosion resistance test: The corrosion-resistant inflatable PVC films prepared in Examples 1-12 and Comparative Examples 1-4 were immersed in a 40 wt % sodium hydroxide aqueous solution for 2 days, and then dried at 80° C. to measure the tensile strength of the PVC films.

[0048] Flame retardant performance test: The corrosion-resistant inflatable PVC films prepared in Examples 1-12 and Comparative Examples 1-4 were tested with reference to the test method for fire rating in UL94-2009.

[0049] According to the data comparison of Examples 1-4 and Comparative Examples 1-4, it can be obtained that PVC is used as the substrate, and the phenolic resin uniformly disperses the modified titanium dioxide on the surface of the PVC, so that the modified nano titanium dioxide is not easy to agglomerate, and the modified titanium dioxide is grafted with maleic anhydride polypropylene and KH550 to improve the compatibility and dispersibility of the nano titanium dioxide with the PVC substrate, thereby further improving the corrosion resistance of the PVC substrate.

[0050] According to the data comparison of Examples 3-6, it can be obtained that when nano-titanium dioxide, KH550 and maleic anhydride grafted polypropylene are in a specific weight ratio, nano-titanium dioxide is not easy to agglomerate, nano-titanium dioxide can be better dispersed and combined with maleic anhydride grafted polypropylene, the two have better compatibility, which helps to reduce the porosity of the PVC film, thereby improving the corrosion resistance of the PVC film.

[0051] According to the data comparison of Examples 6-8, it can be obtained that PVC and stearate are compounded by a physical blending method, nano calcium carbonate has a large specific surface area, can be effectively dispersed on the surface of PVC, and form a good interface bonding, dioctyl terephthalate is compatible with PVC molecules, reduces the interaction force between PVC molecules, increases the plasticity of PVC, and helps to improve the chemical corrosion resistance of PVC; and calcium stearate can interact with the polar groups on the PVC molecular chain through chemical bonding, improve the thermal stability of PVC, reduce the thermal decomposition of PVC during processing, and thus improve the corrosion resistance of the PVC film.

[0052] According to the data comparison of Examples 8-10, when PVC, dioctyl terephthalate, nano-calcium carbonate and calcium stearate are in a specific weight ratio, the four cooperate together and increase the amount of calcium stearate. The lubricating effect of calcium stearate can make PVC less likely to adhere during the processing, and at the same time, it can wetting the nano-calcium carbonate, so that the fluidity of the nano-calcium carbonate is improved, and it can be evenly distributed in the PVC, so that the mechanical strength and thermal stability of the modified PVC are further improved.

[0053] According to the data comparison of Examples 1-12, the modified nano-titanium dioxide is modified by maleic anhydride grafting polypropylene, and the hydroxyl and amino groups in the phenolic resin can react with the anhydride groups in the maleic anhydride to connect the maleic anhydride grafted polypropylene with the modified nano-titanium dioxide; at the same time, the phenolic resin interacts with the polar groups on the PVC chain, thereby enhancing the compatibility between PVC and nano-titanium dioxide, thereby improving the mechanical properties and thermal stability of the PVC film.

Claims

1. A corrosion-resistant inflatable PVC membrane, characterized in that: The invention comprises the following raw materials in parts by weight: 80-120 parts of PVC; 20-40 parts of plasticizer; 10-20 parts of stabilizer; 10-20 parts of modified nano titanium dioxide; 5-15 parts of phenolic resin; the modified nano titanium dioxide comprises nano titanium dioxide, KH550, maleic anhydride grafted polypropylene and deionized water.

2. The corrosion-resistant inflatable PVC membrane according to claim 1, characterized in that: The preparation method of the modified nano titanium dioxide is as follows: 20-30 parts by weight of nano titanium dioxide, 10-15 parts by weight of KH550, 55-70 parts by weight of maleic anhydride grafted polypropylene and 20-40 parts by weight of deionized water are stirred at a speed of 500-600 r / min for 5-10 minutes, and the modified nano titanium dioxide is obtained after filtering and drying.

3. The corrosion-resistant inflatable PVC membrane according to claim 2, characterized in that: The weight ratio of the nano titanium dioxide, KH550 and maleic anhydride grafted polypropylene is 1: (0.48-0.56): (1.28-1.44).

4. The corrosion-resistant inflatable PVC membrane according to claim 2, characterized in that: The particle size of the nano titanium dioxide is in the range of 800-1000 meshes.

5. The corrosion-resistant inflatable PVC membrane according to claim 1, characterized in that: The PVC is modified PVC, wherein the preparation method of the modified PVC is: after mixing 80-120 parts by weight of PVC and 50-70 parts by weight of dioctyl terephthalate for 10-20 minutes, adding 2-8 parts by weight of nano calcium carbonate, heating to 100-120° C. and continuing to stir for 5-10 minutes, then adding 1-3 parts by weight of calcium stearate and stirring evenly, cooling to 60-65° C. and plasticizing for 5-10 minutes to obtain the modified PVC.

6. The corrosion-resistant inflatable PVC membrane according to claim 5, characterized in that: The weight ratio of the PVC, dioctyl terephthalate, nano calcium carbonate and calcium stearate is 1: (0.64-0.66): (0.056-0.072): (0.012-0.015).

7. The corrosion-resistant inflatable PVC membrane according to claim 5, characterized in that: The weight ratio of the modified PVC, modified nano titanium dioxide and phenolic resin is 1: (0.16-0.18): (0.06-0.08).

8. The corrosion-resistant inflatable PVC membrane according to claim 1, characterized in that: The plasticizer is selected from one of dioctyl phthalate and dioctyl adipate.

9. The corrosion-resistant inflatable PVC membrane according to claim 1, characterized in that: The stabilizer is selected from one of barium stearate and zinc stearate.

10. A method for preparing a corrosion-resistant inflatable PVC membrane, characterized in that: The method for preparing the corrosion-resistant inflatable PVC film according to any one of claims 1 to 9 comprises the following steps: mixing and stirring PVC, a plasticizer, a stabilizer, modified nano titanium dioxide and a phenolic resin, plasticizing and refining the mixture, calendering, cooling and winding the mixture after extrusion to obtain the corrosion-resistant inflatable PVC film.

Citation Information

Patent Citations

  • Stable-performance plastic formula

    CN107759931A

  • High-flame-retardance polyvinyl chloride resin and preparation method thereof

    CN108047603A

  • Pvc (polyvinyl chloride) heat-shrinkable film and preparation method thereof

    CN109880253A